Testing Honey on Chicken Embryos as Candidates for Herbal Medicine in Indonesia - Mafruchati, Maslichah; Makuwira, Jonathan (PCJN: Pharmaceutical and Clinical Journal of Nusantara, 2022)
The nutrients in honey had function as antioxidants. The aim of this study was to testing honey on chicken embryos as candidates for herbal medicine in Indonesia. This study used treatment method, consisting of 6 (six) doses of honey products. The solution volume of each treatment dose was fixed at 10 l/egg via the route to the air bag. At the age of 13 days, embryo morphology and possible abnormalities were observed in all treatments. Each two eggs are cracked. The remainder was continued by incubation in the incubator until day 21. During this time the eggs were observed and the number was recorded to find out which eggs would die and which eggs would hatch at the end of the incubation period. Newborn chicks (DOC) were weighed and observed for possible morphological abnormalities. From the results of the research conducted, it was found that the percentage of viable chicken eggs sprouted after being injected with honey (days 13-21 after inoculation) and the morphology of chicken embryos after being injected with honey. Chicken Embryo Weight and Body Length Measurements were carried out in chicken embryos. The conclusion of the study is that propolis from honey products can be used as herbal medicine.